POLITIK HUKUM TERHADAP KOPERASI INDONESIA - Agus Bambang Nugraha (Universitas Kristen Satya Wacana, 2016)
Cooperatives are economic institutions whose existence is mandated by the 1945Constitution of Article 33 paragraph (1) of the 1945 Constitution states that: